2015
DOI: 10.1097/pec.0000000000000351
|View full text |Cite
|
Sign up to set email alerts
|

APACHE Score, Severity Index of Paraquat Poisoning, and Serum Lactic Acid Concentration in the Prognosis of Paraquat Poisoning of Chinese Patients

Abstract: Many prognostic indictors have been studied to evaluate the prognosis of paraquat poisoning. However, the optimal indicator remains unclear. To determine the value of the Acute Physiology and Chronic Health Evaluation II (APACHE II) score, the Severity Index of Paraquat Poisoning (SIPP), and serum lactate levels in the prognosis of paraquat poisoning, we performed a prospective study that enrolled 143 paraquat patients. Data were collected from patients (161) at West China Hospital in Chengdu, China, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…1 ). Ten studies were published in English [ 8 , 11 , 19 26 ] and 19 studies were published in Chinese, [ 27 – 45 ] as shown in Table 1 . Twenty-seven studies were conducted in Chinese and 2 studies in Korean.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 ). Ten studies were published in English [ 8 , 11 , 19 26 ] and 19 studies were published in Chinese, [ 27 – 45 ] as shown in Table 1 . Twenty-seven studies were conducted in Chinese and 2 studies in Korean.…”
Section: Resultsmentioning
confidence: 99%
“…The cutoff value of the APACHE II score was ≥10 in 7 of the studies. [ 8 , 19 , 20 , 24 , 25 , 32 ] The pooled sensitivity of the APACHE II score ≥10 for predicting mortality was 88% (95% CI 71%–95%), and the pooled specificity was 84% (95% CI 67%–93%; Fig. 6 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When doctors recognize the degree of toxicity of PQ poisoning in patients sufficiently early, they can prescribe specific and targeted treatments efficiently and potentially save the patient's life. The mortality rate of PQ poisoning is highly correlated with PQ concentrations [29]; however, there is no recognized method of comprehensively evaluating the relationship of clinical indexes with PQ poisoning. There is a particular lack of knowledge regarding the clinical implications of BRT in PQ poisoning.…”
Section: Discussionmentioning
confidence: 99%